Rethinking Diversity beyond Catalogue Representation: Lessons from Efforts to Develop a Methodology to Evaluate Diversity within the National Library of Australia. Issue 1 (2nd January 2021) - Harrington, Morgan
ABSTRACT: This paper outlines the methodological approaches taken to evaluate the National Library of Australia's (NLA) collection for its representation of culturally and linguistically diverse (CALD) Australians. Firstly, a quantitative method of catalogue evaluation – the 'catalogue method' – in which the NLA's catalogue was systematically searched using terms derived for the Australian Census of Population and Housing, is presented. The limitations of this method, which included a high number of misleading results, and an inability to capture the complexity of cultural identities through simple search terms, are then discussed. With these limitations established, this paper proposes an alternative approach to evaluating the Library as a 'living institution', the aim of which would be to establish how well the NLA serves the needs of CALD Australians. Results of a preliminary attempts at such an evaluation are presented, but an evaluation using this method was not systematically carried out because of time and other resource limitations. By discussing the outcomes of this pilot project, and presenting key findings, this paper aims to provide an informed starting point for any similar future research.